The impact of growth and innovation clusters on unemployment in US metro regions*. Issue 1 (5th April 2017) - Lambert, Thomas E.; Mattson, Gary A.; Dorriere, Kyle
Abstract: Much has been written by various scholars and practitioners over the years about the benefits of industrial clustering. The benefits of such clustering or local agglomeration economies supposedly include greater regional exports, greater employment growth, greater payroll growth, and greater new business establishment creation, among other impacts. However, the work for this article has not uncovered much if any literature on how agglomeration affects United States regional unemployment rates. Additionally, most growing industrial and innovation clusters over the last two decades or so require highly educated and skilled workers. Since most of the unemployed at any given time tend to be less educated and less skilled than most workers on average, any local and state economic development policies that focus on clustering must be careful in targeting lower unemployment rates as a policy goal or outcome. From a theoretical point of view, if greater clustering leads to greater employment growth and employment levels then greater clustering in a US metro area should yield lower unemployment rates than those which have lesser degrees of industry clustering on average. On the other hand, greater clustering and greater industry concentration in either declining industries or in those industries not in decline but at the same time not immune to bad cyclical downturns could yield greater unemployment rates and levels in metro areas which have these types of industries. Therefore, before pursing any policies which promote greater industry clustering, it would be useful for policy‐makers to know whether greater industry clustering or greater industry diversity makes a difference when it comes to unemployment rates for metro areas, which are usually defined as local job markets for most workers. This paper finds that, in general, greater clustering for 'growth and innovation' industries leads to lower unemployment rates in US metro areas, on average, after controlling for other factors which may impact local unemployment rates.